Role of glycogen availability in sarcoplasmic reticulum Ca2+ kinetics in human skeletal muscle - Ørtenblad, N.; Nielsen, J.; Saltin, B.; Holmberg, H. C. (Journal of Physiology, 2011)
Glucose is stored as glycogen in skeletal muscle. The importance of glycogen as a fuel during exercise has been recognized since the 1960s; however, little is known about the precise mechanism that relates skeletal muscle glycogen to muscle fatigue. We show that low muscle glycogen is associated with an impairment of muscle ability to release Ca2+, which is an important signal in the muscle activation. Thus, depletion of glycogen during prolonged, exhausting exercise may contribute to muscle fatigue by causing decreased Ca2+ release inside the muscle. These data provide indications of a signal that links energy utilization, i.e. muscle contraction, with the energy content in the muscle, thereby inhibiting a detrimental depletion of the muscle energy store.